2015
DOI: 10.3389/fpsyg.2015.00982
|View full text |Cite
|
Sign up to set email alerts
|

Can an intervention based on a serious videogame prior to cognitive behavioral therapy be helpful in bulimia nervosa? A clinical case study

Abstract: Background: Several studies have highlighted the implications of impulsivity and novelty seeking for both the maintenance and the process of recovery from bulimia nervosa (BN). Cognitive behavioral therapy (CBT) is the treatment of choice for BN, but for some cases, this treatment alone might not be sufficient for reducing the high levels of impulsivity. The paper presents a case report of a patient with BN, examining the effectiveness of using a videogame (VG; Playmancer) as an additional intervention designe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 65 publications
1
29
1
1
Order By: Relevance
“…These findings are in line with prior research (Bean et al, 2008;Støving et al, 2011;Strober et al, 2006), but they are in disagreement with other studies indicating similar outcomes for men and women with ED (Fernández-Aranda et al, 2009b;Gueguen et al, 2012;Weltzin et al, 2015). Such interventions could potentially enhance treatment adherence and overall therapeutic results (Fernández-Aranda et al, 2015;Giner-Bartolomé et al, 2015). Also, because most studies have assessed patients in residential or inpatient treatment settings, their findings might be slightly inflated because of increased comorbidity and symptom severity in men who need intensive treatment.…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…These findings are in line with prior research (Bean et al, 2008;Støving et al, 2011;Strober et al, 2006), but they are in disagreement with other studies indicating similar outcomes for men and women with ED (Fernández-Aranda et al, 2009b;Gueguen et al, 2012;Weltzin et al, 2015). Such interventions could potentially enhance treatment adherence and overall therapeutic results (Fernández-Aranda et al, 2015;Giner-Bartolomé et al, 2015). Also, because most studies have assessed patients in residential or inpatient treatment settings, their findings might be slightly inflated because of increased comorbidity and symptom severity in men who need intensive treatment.…”
Section: Discussioncontrasting
confidence: 44%
“…These findings suggest that more impulsive patients, both men and women, would benefit from alternative interventions that successfully reduce impulsivity. Such interventions could potentially enhance treatment adherence and overall therapeutic results (Fernández-Aranda et al, 2015;Giner-Bartolomé et al, 2015). However, if we consider the results obtained using the RCI (clinical significant change) criterion, novelty seeking does not list as predictor of improvement in women with ED.…”
Section: Discussionmentioning
confidence: 99%
“…Specific adjuvant interventions to address the facets of impulsivity associated with GD severity could potentially improve treatment outcomes 4,5 . In this sense, technologically based interventions represent a new frontier for treatment, from the computerized adaptation of neurocognitive tasks to evaluate these processes, such as cognitive and attentional bias 81 , to the use of mobile applications to condition the selection of healthy foods obesity 82 , or serious games for the treatment of impulsivity in gambling disorder 83 , in eating disorders 84,85 and in other mental disorders 86 . It has been observed that the use of therapeutic video games, as an additional therapeutic tool can treat difficulties in emotional regulation and impulsivity 84 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the study sample was extremely small (nine individuals) and had varying diagnoses and symptom presentation; thus, the study’s findings may not be generalizable and further replication in larger treatment samples is warranted before meaningful conclusions can be drawn. A single case study also utilized a computerized videogame to enhance inhibitory control prior to engaging in CBT for one patient with BN and reported within-subject decreases in impulsivity as well as binge episodes (60). Despite small sample sizes, these studies provide initial evidence for the potential efficacy of a computerized training program aimed at targeted core components of executive functioning and cognitive control which may supplement existing evidence-based treatments for eating disorders.…”
Section: Treatments Targeting Neurocognitive or Executive Function Inmentioning
confidence: 99%